The Role of Professional Judgment in Complex Auditing and Assurance Decisions (gjstudies, 2018)
The landscape of financial reporting and business operations is undergoing aprofound transformation, characterized by the rise of intangible assets, complexfinancial instruments, decentralized organizational structures, and rapidly evolving digital ecosystems. In this environment, the auditing and assurance profession faces a critical paradox: the very standards and detailed guidelines designedto ensure quality and consistency may be insufficient, or even counterproductive,when applied to novel, ambiguous, and highly complex situations. The ultimatesafeguard in these frontier areas of practice is the professional judgment of theauditor. Yet, the cognitive architecture of this judgment—how it is formed,exercised, and optimized under conditions of extreme complexity—remains inadequately understood. Traditional research has often treated judgment as abinary outcome, correct or biased, focusing predominantly on identifying andmitigating cognitive pitfalls such as confirmation bias or anchoring. This paperargues for a fundamental shift in perspective. We propose that professional judgment in complex contexts is better understood not as a discrete event prone toerror, but as a dynamic, adaptive capability—a complex system in itself. Ourresearch is driven by a primary question: What are the constituent elementsand interactive processes that characterize high-quality professional judgmentwhen auditors navigate decisions that lack clear referents in existing standardsor prior experience? To answer this, we draw upon unconventional methodologies from complex systems theory, cognitive neuroscience, and narrative psychology, constructing a new theoretical model and testing it through immersivesimulation. This approach offers a fresh lens, moving beyond the audit judgment literature’s traditional focus on heuristics and biases towards a holistic,capacity-oriented framework. We contend that enhancing audit quality in the21st century requires a deeper scientific understanding of how expert judgmentsystems function at their best, not just how they fail.